2009
DOI: 10.2166/wh.2009.203
|View full text |Cite
|
Sign up to set email alerts
|

Supply system factors associated with microbiological drinking water safety in regional New South Wales, Australia, 2001–2007

Abstract: Aim: To determine factors associated with microbiological safety of public drinking water systems in regional New South Wales (NSW), Australia.Method: We analysed 107,000 end-user drinking water samples for an association between detection of Escherichia coli and drinking water system features, sample year and season using NSW Health Drinking Water Monitoring Program data, 2001-2007. We used negative binomial generalized estimating equations with adjustment for autocorrelation and clustering.Results: We detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As an example, small water systems experience water quality and service delivery problems more often than larger systems due to the lack of economies of scale (Allaire et al, 2018; Cretikos et al, 2009; McFarlane and Harris, 2018). This is of particular concern when considering that small water systems frequently serve rural, low-income communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, small water systems experience water quality and service delivery problems more often than larger systems due to the lack of economies of scale (Allaire et al, 2018; Cretikos et al, 2009; McFarlane and Harris, 2018). This is of particular concern when considering that small water systems frequently serve rural, low-income communities.…”
Section: Discussionmentioning
confidence: 99%
“…The high risks that some populations may face are subsumed when they are averaged in with the general population receiving high-quality water services. Among studies identified in this review, only Haass et al (Haass et al, 1996) As an example, small water systems experience water quality and service delivery problems more often than larger systems due to the lack of economies of scale (Allaire et al, 2018;Cretikos et al, 2009;McFarlane and Harris, 2018). This is of particular concern when considering that small water systems frequently serve rural, low-income communities.…”
Section: Lack Of Estimates Focusing On Specific Sub-populationsmentioning
confidence: 99%
“…Among studies identified in this review, only Haass et al 27 and Beaudeau et al 28 As an example, small water systems experience water quality and service delivery problems more often than larger systems due to the lack of economies of scale. [29][30][31] This is of particular concern when considering that small water systems frequently serve rural, low-income communities. Allaire et al found that violations of health-based drinking water standards in the US often occur in low-income rural areas.…”
Section: Insufficient Spatial Resolutionmentioning
confidence: 99%
“…A review of 107 000 samples collected from 2001 to 2007 found that systems with inadequate disinfection or serving small populations were more vulnerable to contamination. 5 Almost 40% of systems did not meet the target (i.e. no more than 2% of samples positive) for the faecal indicator Escherichia coli.…”
Section: Nsw Drinking Water Monitoring Programmentioning
confidence: 99%